Antimicrobial susceptibility of Helicobacter pylori isolates in Smolensk in 2015-2016 - N. N. Dekhnich; N. V. Ivanchik; R. S. Kozlov; A. V. Alimov; A. V. Lukyanova; O. A. Nagaeva; A. S. Steshits; P. G. Bruk (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To determine antimicrobial susceptibility of H. pylori in Smolensk in 2015-2016. Material and methods. Overall 248 adult patients with positive rapid urease test at the time of gastroscopy were included in the study. Antimicrobial susceptibility testing of H. pylori isolates to clarithromycin, amoxicillin, metronidazole, levofloxacin, rifampicin, tetracycline was performed by the agar dilution method. Results. H. pylori was isolated in 33% (n=82) of patients (24 isolates were nonviable after freezing). The rates of resistance among tested isolates of H. pylori were: 3,5% (2/58) for clarithromycin, 3,5% (2/58) for amoxicillin, 10.3% (6/58) for metronidazole, 27,6% (16/58) for levofloxacin, 8.6% (5/58) for rifampicin. No isolates showed resistance to tetracycline. Among 58 H. pylori isolates 29% (17 isolates) were resistant to one antimicrobial agent, 12,1% (7 isolates) were resistant to two antimicrobial agents. Associated resistance was observed for levofloxacin and metronidazole 3,5% (2 isolates), levofloxacin and rifampicin 5,2% (3 isolates), metronidazole and rifampicin 3,5% (2 isolates). Conclusions. Smolensk is the area of low clarithromycin resistance. So, clarithromycin-containing regimens are recommended for first-line empirical eradication therapy. Use of levofloxacin is questionable in relation to high levels of resistance H. pylori to levofloxacin. Use of rifabutin is questionable in relation to relatively high H. pylori rifampicin resistance rate.